2019
DOI: 10.3390/agronomy9020071
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Nutrient Management in Rice–Wheat Cropping System: An Evidence on Sustainability in the Indian Subcontinent through Meta-Analysis

Abstract: Over years of intensive cultivation and imbalanced fertilizer use, the soils of the Indiansubcontinent have become deficient in several nutrients and are impoverished in organic matter.Recently, this region has started emphasizing a shift from inorganic to organic farming to managesoil health. However, owing to the steadily increasing demands for food by the overgrowingpopulations of this region, a complete shift to an organic farming system is not possible. The rice–wheat cropping system (RWCS) is in crisis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 39 publications
1
33
0
4
Order By: Relevance
“…Solar radiation, accumulated temperature, and precipitation were the major important meteorological factors that caused wheat grain yield changes from year to year [14,30,[43][44][45]. Hence, it could be explained by the meteorological conditions and potential grain yields in different growing seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar radiation, accumulated temperature, and precipitation were the major important meteorological factors that caused wheat grain yield changes from year to year [14,30,[43][44][45]. Hence, it could be explained by the meteorological conditions and potential grain yields in different growing seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Research [25,26] reported that the wheat grain yields were comparable in the treatments that received 80 t ha −1 yr −1 of organic manure or 204-252 kg N ha −1 yr −1 chemical N-fertilizers. As for biofertilizers, [27][28][29] reported that application of one biofertilizers obtained from sewage sludge at 7.2 L ha −1 increased maize grain yield by 17% compared with the untreated control and [10,30,31] revealed that biofertilizers amendments reduced inorganic N-fertilizers by 25% without decreasing rice yield in India [32].…”
Section: Introductionmentioning
confidence: 99%
“…For comparing SOC and crop yield to show the impact of proper management practice on to bring back the conditions of soil for restoring soil health and ensuring food security, data from supplementary file of database from Sharma et al (2019) was used that involve compared data of integrated nutrient management (INM) and inorganic alone for rice and wheat crop.…”
Section: Study Selectionsmentioning
confidence: 99%
“…Several studies support that organics addition to the soil improves its health as well as ensure food security by managing yield as well as crop quality. Therefore, organics was integrated with inorganic fertilizer termed as INM and was compared with inorganic alone in rice and wheat crops (Sharma et al ., 2019) and the finding suggests that organics addition alongwith inorganic fertilizer improves the rice and wheat yield in most of the condition. The wheat yield was significantly increased in INM treatment over the treatment inorganic alone by 4.5% whereas rice yield was increased by 1.2% ( Figure 5).…”
Section: Effect Of Use Of Organics On Crop Yield and Socmentioning
confidence: 99%
“…However, successful zero tillage after combine-harvested rice is possible only with burning the rice straw and stubbles in rice furrows which may result in uneven sowing due frequent chopping drill and lifting of the drill to clear blockages (11,13). Then, most rice stubbles are burnt in the mechanized rice-wheat systems of Pakistan, as it allows for quick turnaround between crops being rapid and cheap way.…”
Section: Introductionmentioning
confidence: 99%